Analysis of DSTU 8961:2019 in the quantum random oracle model - Kandii, S.O.; Gorbenko, I.D. (Radiotekhnika, 2023)
Modern cryptographic transformations require provable security against a relatively wide class of threats. Typically, such evidentiary security is achieved through formal analysis within the chosen security model. The development of quantum computers led to the emergence of new attack vectors to which classical cryptography was vulnerable. However, there are cryptographic systems that are considered resistant to quantum attacks and some of them are even standardized. The formal analysis of such systems has faced difficulties for a long time, which were associated with the impossibility of applying classical methods of proof to formal models that take into account quantum effects. However, in recent years, many new results have appeared that allow obtaining formal security proofs for quite complex cryptographic transformations, and most of the existing post-quantum asymmetric encryption and key encapsulation schemes currently have corresponding formal proofs within the quantum random oracle model, the most widespread security model for of post-quantum cryptography. DSTU 8961:2019 is the Ukrainian post-quantum standard for asymmetric encryption and key encapsulation. However, security proofs in the quantum random oracle model have not yet been published for it. As part of this work, security evidence was obtained for the design of the key encapsulation mechanism described in DSTU 8961:209. The obtained result is generalized for an arbitrary asymmetric encryption scheme, which may contain decryption errors and can be used to assess the security of not only DSTU 8961:2019, but also other similar asymmetric transformations.